apor Liquid Equilibrium of musts of Agave cocui in a constant pressure - Leal de Pérez, Mayra Carolina; Pérez Camacho, Edgar Enrique; Morán Guillén, Héctor Andrés; Hernández Motzezak, Rómulo José; Pérez Ones, Osney; García López, América (Rev. Téc. Fac. Ing. Univ. Zulia, 2017)
In this research the vapor-liquid equilibrium for Agave cocui fermented musts which constitute a multicomponent complex mixture due to the presence of polar compounds was measured experimentally. Experimental measurements were carried out at constant atmospheric pressure with simple distillation equipment and a gas chromatograph for quantification. The results showed a good correlation exists between the major variables involved in the equilibrium constant pressure (T, P, x, y). The fermented must is considered a mixture with positive deviations from Raoult ideality due the intramolecular interactions and the smaller capacity of its components to form hydrogen bonds. At the same time thermodynamic data have sufficient quality to be used for the simulation of the distillation process, which leads to improving the quality of the alcoholic beverage.